Outcome after intravenous thrombolysis in patients with acute lacunar stroke: An observational study based on SITS international registry and a meta-analysis. Issue 9 (December 2019) - Matusevicius, Marius; Paciaroni, Maurizio; Caso, Valeria; Bottai, Matteo; Khurana, Dheeraj; de Bastos, Mario; Martins, Sheila CO; Krespi, Yakup; Cooray, Charith; Toni, Danilo; Ahmed, Niaz
Background: Intravenous thrombolysis (IVT) for lacunar stroke (LS) is debated, as the underlying pathophysiological mechanism may not be thrombogenic. Aims: To investigate outcomes after IVT in LS in the SITS International Stroke Thrombolysis Register and perform a meta-analysis. Methods: LS was identified by both baseline NIHSS-subscores and discharge ICD-10 codes, and contrasted by IVT to non-IVT treated. IVT patients were predominantly from Europe, non-IVT patients predominantly from South America and Asia. Outcome measurements were functional independence (modified Rankin Scale [mRS] score ≤2), excellent outcome (mRS ≤ 1), and mortality at three months. Matched-control comparisons of symptomatic intracerebral hemorrhage (SICH) between IVT-treated LS and IVT-treated non-LS patients were performed. Additionally, we performed a meta-analysis. Results: Median age for IVT-treated LS patients ( n  = 4610) was 66 years vs. 64 years and NIHSS score was 6 vs. 3, compared to non-IVT-treated LS ( n  = 1221). Univariate outcomes did not differ; however, IVT-treated LS patients had higher adjusted odds ratios (aOR) for functional independence (aOR = 1.65, 95% CI = 1.28–2.13) but similar mortality at three months (aOR = 0.57, 0.29–1.13) than non-IVT-LS. Propensity-score matched analysis showed that IVT-treated LS patients had a 7.1% higher chance of functional independency than non-IVT LS patients ( p  < 0.001). IVT-treated LS patients had lower odds for SICH (aOR = 0.33, 0.19–0.58 per SITS, aOR = 0.40, 0.27–0.57 per ECASS-2) than matched non-LS controls, which was mirrored in the meta-analysis. Conclusions: Our adjusted results show that IVT treatment in LS patients was associated with better functional outcome than non-IVT-treated LS and less SICH than IVT-treated non-LS patients.